Gritos do poder e ecos da resistência: a condicionalidade da educação nos processos de subjetivação do Plano Brasil Sem Miséria - Fick, Maisa Helena Ravanini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This thesis intends to discuss the Brazil Without Poverty Plan and the Bolsa Família conditionality of education and its implication in subjectivity processes of the poor. Poverty has been the target of government policies to condemn millions of Brazilians to the condition of misery and precariousness of life. Alongside this scenario, spread up speeches that affect the poor to social vulnerability, based on a supposed tendency to crime. The intervention on the poor is legitimate, among other reasons, for control of its potentiality, that is, control for what they may do. Among the activities carried out in our society to this control, the conditionality of education is presented as a new form of biopolitics. Thus, the government of life is presented as though it were on the governed and the constraints present in the exercise of power over life are subtly reconfigured in control practices, making them almost imperceptible, given its interpenetration capacity in life. Capture, modeling and disciplining attempts turn to what has become the heart of contemporary capitalism: subjectivity. The production of subjectivity, constituted from their relationship with the world and in this case, to education and its current contours, reconfigures itself, especially when the context of globalized capitalism values the inventiveness of the subject, for their intelligence and flexibility. Education, as one of the conditionalities of the income distribution policies, intervenes in both the individual with his disciplinary apparatus as in the population with its biopolitics technology. This same life, which is the target in the process of production and reproduction for power, is the one that can resist: the power over life resists with the power of life. We propose to approach other education from anarchist principles and its production of subjectivity, aiming at the destruction of hierarchies, authoritarianism, relations of domination and exploitation ...

Este trabalho se propõe a discutir a condicionalidade da educação do Plano Brasil Sem Miséria e do Bolsa Família, bem como sua implicação nos processos de subjetivação da população pobre. A pobreza vem sendo alvo das políticas de Estado por condenar milhões de brasileiros à condição de miséria e precarização da vida. Paralelamente a esse cenário, disseminam-se discursos que condicionam a população pobre à situação de vulnerabilidade social, embasados numa suposta tendência à criminalidade. A intervenção na população pobre, portanto, é legitimada, entre outros motivos, pelo controle de suas virtualidades, isto é, do que os pobres podem vir a fazer. Entre as práticas exercidas em nossa sociedade para esse controle, a condicionalidade da educação apresenta-se como uma nova modalidade de biopolítica. Desse modo, o governo da vida se apresenta como se estivesse a serviço do governado e as coerções presentes no exercício de poder sobre a vida são sutilmente reconfiguradas em práticas de controle, tornando-as quase imperceptíveis, dada sua capacidade de interpenetração na vida. As tentativas de captura, modelização e disciplinarização se voltam ao que se tornou o coração do capitalismo contemporâneo: a subjetividade. A produção de subjetividade, constituída a partir de sua relação com o mundo e, neste caso, com a educação e seus contornos atuais, reconfigura-se quando o contexto do capitalismo globalizado preza pela capacidade inventiva do sujeito, por sua inteligência e flexibilidade. A educação, como uma das condicionalidades das políticas de distribuição de renda, intervém tanto no indivíduo com seu aparato disciplinar quanto na população com sua tecnologia biopolítica. Essa mesma vida, que é visada em seu processo de produção e reprodução pelo poder, é a que pode resistir: ao poder sobre a vida resistimos com a potência da vida. Para tanto, propõe-se abordar outra ...
Keywords: Educação; Subjetividade; Anarquismo e anarquistas; Education; Brasil - Aspectos sociais